Diving into the Slave Wreck: The São José Paquete d'Africa and Yvette Christiansë's Imprendehora. Issue 4 (1st October 2020) - Lavery, Charne
ABSTRACT: The first slave wreck to be definitively identified is the São José-Paquete de Africa, a slave ship from Mozambique Island wrecked off the coast of Cape Town. This paper takes that wreck as case study and context for the southern slave geographies and elongated histories addressed also in Yvette Christiansë's Imprendehora. Both memorialise the 'long middle passage' — between east Africa and South America across the Southern Hemisphere, and well into the nineteenth century — in different ways. But, similarly, they highlight archival gaps, embodiment, and the submarine. Drawing on Toni Morrison's 'literary archaeology', this paper poses a meeting between literary and maritime archaeology, and explores the methodological possibilities of submersion.